Arthroscopic Repair of the Medial Meniscal Root Tear: A Simple Surgical Technique - Mohammad Ayati Firoozabadi, M.D.; Seyed Mohammad Milad Seyedtabaei, M.D.; Hesan Rezaee, M.D.; Omid Salkhori, M.D.; Seyed Mohammad Javad Mortazavi, M.D. (Arthroscopy Techniques)
Medial meniscal root tears pose significant challenges in orthopaedic practice, disrupting knee biomechanics and predisposing to degenerative changes. This article introduces an arthroscopic repair technique tailored for posterior root tears of the medial meniscus. The procedure involves meticulous preoperative evaluation, arthroscopic identification, and suture anchor fixation to restore normal knee mechanics. Inclusion and exclusion criteria ensure suitability, whereas postoperative care emphasizes early rehabilitation. By elucidating the surgical technique and outlining clinical implications, this article aims to equip surgeons with effective strategies for managing this challenging orthopaedic condition.